Prosody and prosodic models - Shih, C; Kochanski, G (2002)
The tutorial will summarize the state of the art of prosody research with an emphasis on intonation ($f_0$). We will present it in a data and knowledge driven fashion, starting with physiology and speech data and building towards theoretical descriptions. We will cover a wide range of intonation phenomenon, discussing the variations, the cause of variations, and their implications to prosodic modeling. Major concepts that will be addressed are: *** The physical bases of prosody: what gestures and acoustic features carry information, and how the acoustics relate to physiology. *** Prosody as a communications channel ** Accents and tones ** . Intonation type (Question vs. declarative ldots) ** Focus, prominence,. discourse segments, {em etc} ** Prosody used to convey emotion ** . Prosody tied to the physical system: declination . *** A survey of algorithms for modeling prosody. We will comment on the strengths and limitations of a variety of theories and modeling techniques. ** Basic Questions: * How is all this information carried on a shared channel? * How is it encoded? * How much of prosody can be predicted from text? ** Intonation Models. * Some models describe prosody as a single composite signal, others as discrete signals. ** Duration.